Research of the Competition Level for Manufacturers and Distributors of the Pharmaceutical Market in Ukraine - Kosteniuk, Yu. B.; Popenko, A. M. (Statistics of Ukraine, 2023)
The article analyzes the development of the pharmaceutical market of Ukraine, proves the prospects of this industry in terms of the impact on the national economy and indicators of dynamics in the period from 2018 to 2021. During this period, the influence of global processes on the dynamics of the production indicators and sale of goods in the pharmaceutical market, the impact of the COVID pandemic is assessed and its consequences, as well as the beginning of a full-scale war of the RF against Ukraine. A retrospective study about the development of the main players of the pharmaceutical market in Ukraine at all levels of the medical products-representatives movement: from production to distribution of products by distributors, taking into account the national and foreign affiliation of a specific counterparty. The level of market monopolization was evaluated according to the Lind and Herfindahl-Hirschman indices, which are the most common methods among scientists for identifying the level of market concentration. It is illustrated that newly created and small enterprises of the pharmaceutical market, which constitute a competitive environment in the industry, deserve special attention. According to the results of the analysis, enterprises with an extremely high level of market concentration for manufacturers and distributors were also identified: “Farmak” and “Darnytsia” and “Optima-Pharm LTD” and “BaDM”, respectively. Among the manufacturers, a comparative analysis of structures in dynamics using the coefficient of structural shifts was additionally applied - to generalize the intensity of changes for 2021 and 2022. In the structure of distributors, particular attention is also paid to the enterprise «Venta LTD», which closes the top three enterprises in the farm industry, but has a risk of nationalization due to the share of Russian capital in the total assets of the enterprise, which gives time to other suppliers to occupy places on the trade niches, forming an oligopoly on market. As a result, specific decisions regarding state regularization as a way to solve the problem of pharmaceutical market monopolization by some of its representatives, related to the main principles of ensuring a competitive environment: transparency, control, support and protection of enterprises, are given to the conducted analysis. The specified information constitutes a promising direction of research – cooperative relations between manufacturers and distributors for the establishment of a logistics chain in today’s conditions.